The case of ineffective conservative treatment of endometriosis of anterior abdominal wall from the point of view of the possible role of stem cells - S O Dubrovina; Yu D Berlim; V S Gimbut; L V Krasilnikova; K A Areshyan; A I Lukash (IP Berlin A.V., 2017)
The article highlights the pathogenetic mechanisms of endometriosis outside the peritoneal cavity from the point of view of the role of bone marrow stem cells, given a possible explanation for the low efficiency of drug therapy of endometriosis outside the peritoneal cavity. The paper presents our own experience of using agonist of gonadotropin-releasing hormone intrauterine device with levonorgestrel at the same time.